The proposal of norms of international judicial competence in matters of parenthood: between the known and the unknown - Durán Ayago, Antonia (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The rules of international judicial jurisdiction included in the Proposal for a Regulation on parentage move between well-known forums, many of them rescued from Regulation (EU) 2019/1111 on parental responsibility, but without the due adjustments, and novel forums such as the one related to the Member State of birth of the son. The forum necessitatis could be a forum of protection/refuge for families from third States that could not be recognized as such in their States of origin.
Keywords: Parenthood; international judicial jurisdiction; free movement of people; principle of mutual recognition